Efficient Experimental Design with Marketing Research Applications - Kuhfeld, Warren F.; Tobias, Randall D.; Garratt, Mark (Journal of Marketing Research, 1994)
The authors suggest the use of D-efficient experimental designs for conjoint and discrete-choice studies, discussing orthogonal arrays, nonorthogonal designs, relative efficiency, and nonorthogonal design algorithms. They construct designs for a choice study with asymmetry and interactions and for a conjoint study with blocks and aggregate interactions.